A Rare Case of Hemoperitoneum Diagnosed with Point of Care Ultrasound (POCUS) - Jina Bai; Todd Cutler (POCUS Journal)
A 68-year-old man presented with one week of vague abdominal symptoms and was found to have new ascites and pulmonary embolism for which a heparin drip was initiated. We report a case diagnosing hemoperitoneum with point of care ultrasound (POCUS). Identifying hemoperitoneum can be challenging, but POCUS can be a useful tool for its diagnosis. There is limited literature on the sonographic characteristics of hemoperitoneum. Echogenicity of fluid is not a reliable distinguisher between exudative and transudative effusions. The diagnosis of hemoperitoneum in this case was suggested by the progression of POCUS findings over time rather than sonographic characteristics by themselves.